Sustainable Tourism Integrated Tourism Area Based on Culture and Local Wisdom at Mandeh Area - Siti Fatimah; Dewi Ramadhan (The Tourism, Heritage and Recreation Sport Center, Universitas Negeri Padang, 2019)
The purpose of this research to (1) identify the forms of culture (tradition) and local wisdom possessed by the Mandeh community, (2) filter out any culture (tradition) that can be developed for sustainable tourism in the integrated Integrated Tourism Area. The method used in this study is a qualitative method with an ethnography analysis model. Research informants are community leaders and people who can provide information about various cultures and local wisdom in the Mandeh region. The data collection tool uses instruments such as interviews, observations, recording devices, and TOR and FGD instruments. Data collection techniques were carried out through interviews, documentation, observation and focus group discussions. The results of this study are (1) the forms of traditional culture found in the Integrated Mandeh Tourism Area are: balimau kasai tradition, gamat, Puti Andam Dewi folklore, mamukek tradition, randai and dance, badie-badie tomong, basanji, tukang canang, and mutual cooperation. (2) Traditional culture that can be developed for sustainable tourism is balimau kasai, gamat, mamukek and randai.